2015
DOI: 10.1111/ajt.13012
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Development of CMV-Specific CD8+ T cell Response in CMV-Seropositive Solid Organ Transplant Candidates

Abstract: This cross-sectional study analyzes factors associated with the development of CMV-specific CD8þ response, measured by IFNg production after cytomegalovirus (CMV) peptide stimulation, in CMV-seropositive solid organ transplantation candidates. A total of 114 candidates were enrolled, of whom 22.8% (26/114) were nonreactive (IFNg < 0.2 IU/mL). Multivariate logistic regression analysis showed that age, HLA alleles and organ to be transplanted were associated with developing CMV-specific CD8þ immunity (reactive; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
(50 reference statements)
3
12
1
Order By: Relevance
“…We would like to thank Fern andez-Ruiz et al (1) for their interest in our manuscript (2) and welcome the opportunity to address their comments on the factors influencing CMVspecific T cell response in transplant candidates.…”
Section: To the Editormentioning
confidence: 99%
“…We would like to thank Fern andez-Ruiz et al (1) for their interest in our manuscript (2) and welcome the opportunity to address their comments on the factors influencing CMVspecific T cell response in transplant candidates.…”
Section: To the Editormentioning
confidence: 99%
“… SOT setting: Although there are only a few studies testing CMV‐specific CMI before SOT, all of them coincide in its utility for individualizing the post‐transplantation risk of CMV infection. Cantisan et al demonstrated that patients lacking pretransplant CMI (ie, nonreactive QuantiFERON‐CMV test) were more likely to develop post‐transplant CMV replication than those with a reactive assay at that point . Ritta et al and Bestard et al found that having low pretransplant CMV‐specific T‐cell responses was associated with a higher risk of post‐transplant CMV replication .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of humoral immunity, cellular immunity is considered more important in the virus control [1], with both CD8+ cytotoxic and CD4+ helper cells playing a central role in the resolution of acute infection and in the maintenance of long-term memory. In vitro studies demonstrated the association between production of IFN-gamma by the CD8 T lymphocytes and the risk of infection/CMV disease after transplantation [2], [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%